Ultrastructural evidence for an unusual mode of ciliogenesis in mouse multiciliated epithelia. (1st December 2020) - Narita, Keishi; Takeda, Sen
Abstract: Multiciliogenesis is a cascading process for generating hundreds of motile cilia in single cells. In vertebrates, this process has been investigated in the ependyma of brain ventricles and the ciliated epithelia of the airway and oviduct. Although the early steps to amplify centrioles have been characterized in molecular detail, subsequent steps to establish multicilia have been relatively overlooked. Here, we focused on unusual cilia-related structures previously observed in wild-type mouse ependyma using transmission electron microscopy and analyzed their ultrastructural features and the frequency of their occurrence. In the ependyma, 5% of cilia existed as bundles; while the majority of the bundles were paired, bundles of more than three cilia were also found. Furthermore, apical protrusions harboring multiple sets of axonemes were occasionally observed (0–2 per section), suggesting an unusual mode of ciliogenesis. In trachea and oviduct epithelia, ciliary bundles were absent, but protrusions containing multiple axonemes were observed. At the base of such protrusions, certain axonemes were completely enwrapped by membranes, whereas others remained incompletely enwrapped. These data suggested that the late steps of multiciliogenesis might include a unique process underlying the development of cilia, which is distinct from the ciliogenesis of primary cilia.